Badania ankietowe jako forma konsultacji społecznych władz lokalnych na przykładzie gminy Marciszów - Zawierucha, Stefan (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In this article the author tried to lead some social consultations because he assumed that proper monitoring of the social opinion in the era of considerable increasing of the scope of the local self- government means a lot in relations between the communal organs and the society. This examination was led in the commune of Marciszów situated in the south- west of Poland, Lower Silesian voivodship. From among many methods and techniques of communication such as meetings, personal conversations, press publications or village gatherings, the author has decided on questionnaires at the most believable, because this examination was led anonymously. For a long time it has been known that every citizen who is convinced of the fact that nobody will recognise the author of a certain opinion, will give much more and honest information about in what way some activities should be led. Hence, this article and the results of the examination included in it, which will allow making right decisions in the future with a benefit for the inhabitants, are an example of this. Additionally, every form of social consultations between the authority an the society, especially the one giving a possibility of a full and unembarrassed voice, is a basis of democracy and social subjectivity. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 383-399